Synthesis and Structural Characterization of Hexacoordinate Silicon, Germanium, and Titanium Complexes of the E. coli Siderophore Enterobactin. Issue 32 (2nd July 2013) - Baramov, Todor; Keijzer, Karlijn; Irran, Elisabeth; Mösker, Eva; Baik, Mu‐Hyun; Süssmuth, Roderich
Abstract The E. coli siderophore enterobactin, one of the strongest FeIII chelators known to date, is also capable of binding SiIV under physiological conditions. We report on the synthesis and structural characterization of the tris(catecholate) SiIV–enterobactin complex and its GeIV and TiIV analogues. Comparative structural analysis, supported by quantum‐chemical calculations, reveals the correlation between the ionic radius and the structural changes in enterobactin upon complexation.